Influence of salt dissolution on durable performance of asphalt and Self-ice-melting asphalt mixture. (5th September 2022) - Guo, Runhua; Zhang, Haihu; Tan, Yuanxin
Highlights: Asphalt and asphalt mixtures containing MFL were treated with dry-wet cycles. Engineering properties of asphalt and asphalt mixtures were tested. Influence of salt dissolution on the durability of asphalt and asphalt mixture was investigated. The influence mechanism of salting dissolution on asphalt was analyzed. Abstract: At present, research on the influence of salt dissolution on pavement performance of self-ice-melting asphalt mixture is scarce. Based on laboratory research, this study aims to investigate the influence of salt dissolution on the durable performance of asphalt and self-ice-melting asphalt mixture. Firstly, SBS modified asphalt binder containing Mafilon (MFL) and self-ice-melting asphalt mixture (SMA-13) containing MFL and rubber particles (RP) were subjected to dry-wet cycles for different cycles. Then the influence of salt dissolution on the properties of asphalt and its mechanism were studied by physical properties test, scanning electron microscopy (SEM) test, energy dispersive spectrometer (EDS) test and Fourier transform infrared spectroscopy (FTIR) test. Finally, the influence of salt dissolution degree on long-term pavement performance of asphalt mixture was evaluated by freeze–thaw splitting test, rutting test, and trabecular bending test. The experimental results showed that with the increase in the number of dry-wet cycles, the penetration and ductility of asphalt decrease, while the softening point increases. The greater the content of MFL and the increasing number of dry-wet cycles, the greater the variation is. The effect of salt dissolution on asphalt properties can be attributed to salt aging and physical effect, without chemical reactions occurring. In addition, the road performance test of asphalt mixture indicated that the decrease of water stability, high-temperature performance, and low-temperature performance of self-ice-melting asphalt mixture increases firstly and then tends to be gentle as the increase of salt dissolution. What's more, the water stability is deeply influenced by salt dissolution.